CODE-SWITCHING IN PRUDENCE ANGELINE’S TIKTOK ACCOUNT: A SOCIOLINGUISTIC STUDY - Wita Meilina Laura; Otong Setiawan Djuharie (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to identify and analyze the forms and functions of code-switching in the TikTok content of Prudence Angeline using a sociolinguistic approach. In the current digital era, social media has become a vital platform for individuals to construct self-image and employ communication strategies, including the alternating use of two languages. Drawing on Hoffman’s (1991) theory, this research classifies code-switching into three main types: intra-sentential switching, inter-sentential switching, and emblematic switching. Data were collected from eleven TikTok videos uploaded by Prudence Angeline between April 24 and May 8, 2025. The findings reveal that the most dominant form of code-switching is intra-sentential switching, where the speaker blends Indonesian and English within a single sentence structure in a flexible and natural manner. These findings indicate that code-switching serves not only as a means of communication but also as a strategy for constructing a professional identity and enhancing engagement with a bilingual audience.